Trinodal Self‐Penetrating Versus cds 3‐Dimensional Networks Using Bis(3, 2' : 6', 3''‐terpyridine) Building Blocks: the Solvent Makes the Difference. Issue 12 (8th December 2022) - Capomolla, Simona S.; Manfroni, Giacomo; Prescimone, Alessandro; Constable, Edwin C.; Housecroft, Catherine E.
Abstract: Reactions between Co(NCS)2 and 2 4, 2 4 ‐[2, 5‐bis(cyclohexyloxy)‐1, 4‐phenylene]di(1 3, 2 2 : 2 6, 3 3 ‐terpyridine) (1 ), 2 4, 2 4 ‐[2, 5‐bis(cyclohexylmethoxy)‐1, 4‐phenylene]di(1 3, 2 2 : 2 6, 3 3 ‐terpyridine) (2 ), and 2 4, 2 4 ‐[2, 5‐bis(2‐phenylethoxy)‐1, 4‐phenylene]di(1 3, 2 2 : 2 6, 3 3 ‐terpyridine) (3 ) under conditions of crystal growth by layering at room temperature lead to 3‐dimensional nets with either a cds or trinodal self‐penetrating topology depending upon the solvents (MeOH/C6 H5 Cl, MeOH/1, 2‐Cl2 C6 H5, or MeOH/CHCl3 ) used in the crystallization experiments. The cds network was found for [Co(NCS)2 (1 )] n ⋅2 n C6 H4 Cl2, [Co(NCS)2 (2 )] n ⋅4 n C6 H4 Cl2, and [Co(NCS)2 (3 )] n ⋅2.5 n C6 H5 Cl, while a trinodal self‐penetrating net was observed in [Co2 (NCS)4 (2 )2 ] n ⋅5.5 n CHCl3 ⋅0.2 n MeOH. Preliminary structural data for single crystals from the reactions of Co(NCS)2 and 1 or Co(NCS)2 and 3 from MeOH/CHCl3 solvent combinations also evidenced the assemblies of trinodal self‐penetrating nets. Both net topologies assemble from a combination of planar, 4‐connecting metal and ligand nodes. The role of the solvent in directing the network type is investigated. Abstract :